Improving the Torque Quality of Permanent Magnet Synchronous Motors by Model Advanced Predictive Current Control Method - Văn Thị Kiều Nhi; Lê Văn Đại; Bạch Thanh Quý (Journal of Technical Education Science, 2025)
Drive systems that require high precision often use Permanent Magnet Synchronous Motors (PMSM) due to their high efficiency and reliable operation. However, torque fluctuations and current harmonics in the internal motor are still quite high. This study proposes an improved predictive control model to improve the torque quality as well as reduce the harmonic current in the motor. To reach the control goal and find the best voltage vector for the next control cycle, the proposed predictive current control model uses all three control variables of PMSM at the same time. These are the predictive torque, predictive flux, and predictive current. Matlab/Simulink simulates the proposed control algorithm, revealing its effectiveness in reducing torque ripple and current harmonics in the drive system. Comparing with the FOC (Field Orient Control) method and the conventional model predictive current control, the proposed control solution significantly improves the ability to reduce current harmonics, torque ripples, and response time for PMSM.